Peran Career Adaptability Terhadap Emotional Intelligence Dan Work Values: Literature Review - Deddy Novie Citra Arta; Rivai Makduani; Fahrur Rozi; Muhammad Taufik; Yahya Nusa (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Good employee performance factors are supported by good employee Career Adaptability and Emotional Intelligence abilities. Because the level of achievement of individuals or employees in an organization or company can increase productivity if it is supported by good employee emotions and career adaptations in the work environment. The purpose of this article is to analyze the literature on the Role of Career Adaptability on Emotional Intelligence and Work Values. The research method is in the form of literature study by reviewing various related studies recorded in Mendeley's references and Google Schoolars. The results of this study were analyzed and used as material for discussion to determine answers to problems. The results of the analysis explain that there is a positive and significant role in Career Adaptability on Emotional Intelligence and Employee Work Values. So that it has a positive impact on the success of the company. Keywords: Career Adaptability, Emotional Intelligence, Work Values